Kỹ thuật đặt buồng tiêm dưới da với đường vào tĩnh mạch cảnh trong trong điều trị ung thư vú và ung thư tiêu hoá - Dũng, Nguyễn Việt; Hiệp, Phạm Như; Tùng, Nguyễn Đình; Phúc, Nguyễn Văn; Hồng, Lê Kim (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
AA